2019
DOI: 10.3329/jbcbm.v5i1.42190
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton flora of Tanguar haor ecosystem in Bangladesh: Cyanophyta, Pyrrhophyta, Chrysophyta and Euglenophyta

Abstract: The present paper is dealt with the composition and density of the population of pelagic phytoplankton collected from two studied stations, namely Watch Tower and Rauar Station of Tanguar Haor in Sunamganj District. Plankton belonging to the divisions Cyanophyta, Pyrrhophyta, Chrysophyta and Euglenophyta were studied from bimonthly collected samples during 2017 and 2018. Division Cyanophyta was represented by the occurrence of 17 species followed by Chrysophyta (16 spp.), Euglenophyta (4 spp.) and Phyrrhophyta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The latter compound was recorded >1.0 mg/l, except the Rauar Station of Tanguar Haor. Bhuiyan et al (2)(3)(4)(5) observed the mean water transparency 2.51 m, SRP 17.19 µg/l and chl-a 5.47 in Tanguar Haor (2)(3)(4)(5) , while the measurements carried out in the Hakaluki Haor during the fish kill event were: water transparency 1.24 m, SRP 12.50 µg/l and chl-a 38.05 µg/l. Tanguar Haor has a relatively deeper basin compared to Hakaluki and holding little clearer water, as it is evident by the data on Secchi Disc value and chl-a measured for both the Haors.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The latter compound was recorded >1.0 mg/l, except the Rauar Station of Tanguar Haor. Bhuiyan et al (2)(3)(4)(5) observed the mean water transparency 2.51 m, SRP 17.19 µg/l and chl-a 5.47 in Tanguar Haor (2)(3)(4)(5) , while the measurements carried out in the Hakaluki Haor during the fish kill event were: water transparency 1.24 m, SRP 12.50 µg/l and chl-a 38.05 µg/l. Tanguar Haor has a relatively deeper basin compared to Hakaluki and holding little clearer water, as it is evident by the data on Secchi Disc value and chl-a measured for both the Haors.…”
Section: Resultsmentioning
confidence: 98%
“…In this Haor Basin of Bangladesh, Tanguar Haor has been declared as an Ecologically Critical Area (ECA) by the Government of the People's Republic of Bangladesh and as a Ramsar Site by UNESCO in 1999. The physicochemical condition of this Haor from Rauar and Watch Tower Station were studied (2)(3)(4)(5) .Phytoplankton composition of at least 5 out of 10 algal divisions of this Haor were also worked out (2)(3)(4)(5) . Considering area, the largest haor ecosystem of Bangladesh named Hakaluki is situated in the districts of Moulvibazar and Sylhet.…”
Section: Introductionmentioning
confidence: 99%
“…Including the seasonal floodplain the total aquatic surface area in Bangladesh becomes 36,663 km 2 . A good diversity of plankton and aquatic macrophytes is present in those aquatic ecosystems leading to a substantial amount of freshwater fish production (Bhuiyan et al 2019a(Bhuiyan et al , b, 2021. The diversity of some rare fresh water phytoplankton from Bangladesh (with one new species) is Microcrocis granulata; Paulinella chromatophora; Aphanothece clathrata; Strombomonas acuminata var.…”
Section: Aquaticmentioning
confidence: 99%